Hubungan Screen Time Ibu dengan Perkembangan Bahasa Anak Usia 1–3 Tahun: Studi Eksploratif di Wilayah Kerja Klinik Pratama Unhas Baraya - Nur Aliya Arsyad; Rachmawati Abdul Hafid; Linda Linda; Safaruddin Safaruddin; Misbawati Misbawati (KOLONI, 2026)
Language development in children aged 1–3 years is a critical aspect of child growth and development that is influenced by the quality of parental stimulation and interaction. High gadget use among mothers potentially reduces the quality of verbal interaction through the phenomenon of technoference, which may affect children's language development. This study aimed to analyze the association between maternal screen time and language development in children aged 1–3 years in the working area of Klinik Pratama Unhas Baraya. Methods: This study employed an analytical observational design with a cross-sectional approach. A total of 40 mothers with children aged 12–36 months were selected using consecutive sampling technique. Maternal screen time data were collected using an adapted version of the Screen Time Questionnaire (STQ), while children's language development was assessed using the Kuesioner Pra Skrining Perkembangan (KPSP) specifically on the speech and language domain. Data were analyzed using Fisher's Exact Test with a significance level of p<0.05. Results: The results showed that the majority of mothers had high screen time category (62.5%) and most children demonstrated normal language development (75.0%) . The proportion of language delay was higher in the group of mothers with high screen time compared to those with low screen time (32.0% vs 13.3%) . However, statistical analysis revealed no significant association between maternal screen time and language development in children aged 1–3 years (p=0.269) . Conclusion: Maternal screen time did not show a statistically significant association with language development in children aged 1–3 years. Nevertheless, gadget use among mothers remains a concern as it has the potential to affect the quality of interaction and language stimulation in early childhood.